Melanoma development molecular biology, genetics and clinical application - Bosserhoff, Anja (Springer, 2011)
The book provides comprehensive insights into molecular changes in malignant melanoma. The general mechanisms of melanoma growth and development are described, as well as new research findings. Our current knowledge on the molecules involved in cell transformation and tumor progression will soon lead to sophisticated, targeted therapies. Recent studies with targeted b-RAF inhibitors have given us grounds to hope that these therapies will be successful. Melanoma Development- Molecular Biology, Genetics and Clinical Application aims to contribute to this knowledge. Summarizing the newest data and presenting upcoming research areas in the field, the book will be of great interest to basic researchers and physicians working in the important fields of melanoma, cancer research, therapy and dermatology.